USING AUDIO-VISUAL MATERIALS IN TEACHING FOREIGN LANGUAGE - Umaraliyeva Munojat Mashrabovna; Hafizjonova Mavluda Sherzodbekovna (Journal of new century innovations, 2023)
Annotation: This article is about the effects of audio-visual aids in teaching English active vocabulary to EFL learners. It aims at showing whether audio-visual aids can help learners to use their active vocabulary and discovering teachers’ attitude towards these aids in facilitates the teaching process.